Word Learning by Preschool-Age Children With Developmental Language Disorder: Impaired Encoding and Robust Consolidation During Slow Mapping. - Gordon, Katherine R.; Storkel, Holly L.; Uglow, Stephanie; Ohlmann, Nancy B. (Journal of Speech, Language & Hearing Research, 2021)
Purpose: Learning novel words, including the specific phonemes that make up word forms, is a struggle for many individuals with developmental language disorder (DLD). Building robust representations of words includes encoding during periods of input and consolidation between periods of input. The primary purpose of the current study is to determine differences between children with DLD and with typical development (TD) in the encoding and consolidation of word forms during the slow mapping process. Method: Preschool-age children (DLD = 9, TD = 9) were trained on nine form-referent pairs across multiple consecutive training days. Children's ability to name referents at the end of training days indicated their ability to encode forms. Children's ability to name referents at the beginning of training days after a period of overnight sleep indicated their ability to consolidate forms. Word learning was assessed 1 month after training to determine long-term retention of forms. Results: Throughout training, children with DLD produced fewer forms correctly and produced forms with less phonological precision than children with TD. Thus, children with DLD demonstrated impaired encoding. However, children with and without DLD demonstrated a similar ability to consolidate forms between training days and to retain forms across a 1-month delay. Conclusions: Difficulties with word form learning are primarily driven by deficits in encoding for children with DLD. Clinicians and educators can support encoding by providing children with adequate exposures to target words via robust training that occurs across multiple sessions.